Effects of organizational factors on short term post-IPO operating performance. - Chu, Jasmine Wanling. (2008)
Our research is based on short term post-IPO operating performance change by examining the effects of organizational factors among issuers in Singapore. The implications of our study for firms and potential investors’ assessment of inherent organizational factors of size and age and management’s abilities to deal with the impending changes associated with IPO issue through internal adjustments are discussed.